Analysis of Data Utilization Strategies on Taxpayer Compliance at the Payakumbuh Pratama Tax Service Office - Janita Christina Menndrova; Fajri Adrianto; Fatia Fatimah (Institute of Computer Science (IOCS), 2022)
Taxpayer compliance that has been studied so far is a formal compliance in terms of reporting the Annual SPT. Where the formal compliance is in the form of whether or not the taxpayer has reported the Annual SPT and whether the reporting of the Annual SPT is on time or late. The purpose of this study was to determine the strategy of data utilization on taxpayer compliance at the Payakumbuh Pratama Tax Service Office. In this study using a descriptive method with a qualitative approach. The researcher's data collection technique used interviews. From the results of the study, it was found that the strategy of utilizing taxation data on taxpayer compliance had not yet fully taken the right steps in increasing taxpayer compliance. In this study, it is hoped that it can be used as reference material to add to the literature and develop knowledge about taxpayer compliance. In addition, it can be an evaluation material for the Payakumbuh Primary Tax Service Office to constantly improve and improve the performance and quality of its employees